2017
DOI: 10.1021/acsenergylett.7b00273
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite-Free Lithium Deposition with Self-Aligned Columnar Structure in a Carbonate–Ether Mixed Electrolyte

Abstract: Batteries with lithium metal anodes are promising because of lithium’s high energy density. However, the growth of Li dendrites on the surface of the Li electrode in a liquid electrolyte during cycling reduces the safety and cycle performance of batteries, hindering their commercial application. In this work, we observe for the first time a smooth and dendrite-free Li deposition with a vertically grown, self-aligned, and highly compact columnar structure formed during cycling in a mixed carbonate–ether electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…d) The Li metal plating in EC/DMC at 0.50 mA cm −2 after the 50th cycle (d 1 ), and Li metal in EC/DMC‐30% DME after the 200th cycling at 1 mA cm −2 (d 2 ) and transformation of Li deposits after different cycles (d 3 ). Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: | Liquid Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…d) The Li metal plating in EC/DMC at 0.50 mA cm −2 after the 50th cycle (d 1 ), and Li metal in EC/DMC‐30% DME after the 200th cycling at 1 mA cm −2 (d 2 ) and transformation of Li deposits after different cycles (d 3 ). Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: | Liquid Electrolytementioning
confidence: 99%
“…The rational combination of present ether and carbonate solvent emerges as a fresh attempt to regulate SEI formation and Li deposition . The morphology of Li deposits varies from small and dendritic Li into large dense columnar Li (10 µm in diameter) while adding DME into carbonate electrolyte (Figure d) . The increase of flexible Li organic species (−(CH 2 CH 2 O) n −) and stable inorganic Li salts (Li 2 O and LiF) contributes to this significant change of the morphology of Li deposits.…”
Section: | Liquid Electrolytementioning
confidence: 99%
“…20 Recently, H. Yu et al exhibited a self-aligned columnar structure with smooth and dendrite-free Li deposition in a carbonate-ether mixed electrolyte. 21 R. Xu et al presented an artificial soft-rigid protective layer for dendrite-free Li metal anode. 22 S. Choudhury et al reported a highly reversible Li metal battery based on crosslinked hairy nanoparticles, which can afford enhanced mechanical strength and good ionic conductivity.…”
Section: Rechargeable Lithium Metal Battery Has Been Regarded As One mentioning
confidence: 99%
“…[14] Thed ifference in local ion-solvent structures is believed to give new insights.T hese future insights are expected to revolutionize current electrolyte recipes. [15] Third, since most of the organic solvents are intrinsically reducible by Li and Na while ion-solvent complexes ubiquitously exist in any known electrolyte system, designing an artificial or in situ protective layer on the alkali metal anode to prevent its direct contact to unstable ion-solvent complexes emerges as amore promising…”
mentioning
confidence: 99%